Second autologous stem cell transplantation for relapsed/refractory Hodgkin lymphoma after a previous autograft: a study of the lymphoma working party of the EBMT. Issue 12 (14th October 2020) - Martínez, Carmen; Boumendil, Ariane; Romejko-Jarosinska, Joanna; Anagnostopoulos, Achilles; Faber, Edgar; Poiré, Xavier; Yakoub-Agha, Ibrahim; Akhtar, Saad; Gurman, Gunhan; Pavone, Vincenzo; Halaburda, Kazimierz; Sousa, Aida Botelho; et al.
Abstract: The purpose of this study was to analyze the results of second autologous hematopoietic stem cell transplantation (ASCT2) for patients with relapsed/refractory Hodgkin lymphoma (HL) after a first transplantation (ASCT1). Outcomes for 56 patients receiving an ASCT2 registered in the EBMT database were analyzed. The 4-year cumulative incidences of non-relapse mortality and disease relapse/progression were 5% and 67%, respectively. The 4-year overall survival (OS) and progression-free survival (PFS) were 62% and 28%. In univariate analysis, relapse of HL within 12 months of ASCT1 was associated with a worse OS (35% versus 76%, p = 0.01) and PFS (19% versus 29%, p = 0.059). Chemosensitivity at ASCT2 predicted better outcomes (4-year OS 72% versus 29%, p = 0.002; PFS 31% versus 12%, p = 0.015). This series shows that ASCT2 is a safe procedure and a relatively effective option for patients with late relapses after ASCT1 and with chemosensitive disease who are not eligible for an allogeneic transplant.